Alginates along the filament of the brown alga Ectocarpus help cells cope with stress - Rabillé, Hervé; Torode, Thomas A.; Tesson, Benoit; le Bail, Aude; Billoud, Bernard; Rolland, Elodie; Le Panse, Sophie; Jam, Murielle; Charrier, Bénédicte (Scientific Reports, 2019)
Ectocarpus is a filamentous brown alga, which cell wall is composed mainly of alginates and fucans (80%), two non-crystalline polysaccharide classes. Alginates are linear chains of epimers of 1,4-linked uronic acids, β-D-mannuronic acid (M) and α-L-guluronic acid (G). Previous physico-chemical studies showed that G-rich alginate gels are stiffer than M-rich alginate gels when prepared in vitro with calcium. In order to assess the possible role of alginates in Ectocarpus, we first immunolocalised M-rich or G-rich alginates using specific monoclonal antibodies along the filament. As a second step, we calculated the tensile stress experienced by the cell wall along the filament, and varied it with hypertonic or hypotonic solutions. As a third step, we measured the stiffness of the cell along the filament, using cell deformation measurements and atomic force microscopy. Overlapping of the three sets of data allowed to show that alginates co-localise with the stiffest and most stressed areas of the filament, namely the dome of the apical cell and the shanks of the central round cells. In addition, no major distinction between M-rich and G-rich alginate spatial patterns could be observed. Altogether, these results support that both M-rich and G-rich alginates play similar roles in stiffening the cell wall where the tensile stress is high and exposes cells to bursting, and that these roles are independent from cell growth and differentiation.
CRIS-Team Scopus Importer:2019-09-17

Analysis of the Localization of Fluorescent PpROP1 and PpROP-GEF4 Fusion Proteins in Moss Protonemata Based on Genomic “Knock-In” and Estradiol-Titratable Expression - le Bail, Aude; Schulmeister, Sylwia; Perroud, Pierre-François; Ntefidou, Maria; Rensing, Stefan A.; Kost, Benedikt (Frontiers in Plant Science, 2019)
Tip growth of pollen tubes, root hairs, and apical cells of moss protonemata is controlled by ROP (Rho of plants) GTPases, which were shown to accumulate at the apical plasma membrane of these cells. However, most ROP localization patterns reported in the literature are based on fluorescent protein tagging and need to be interpreted with caution, as ROP fusion proteins were generally overexpressed at undefined levels, in many cases without assessing effects on tip growth. ROP-GEFs, important regulators of ROP activity, were also described to accumulate at the apical plasma membrane during tip growth. However, to date only the localization of fluorescent ROP-GEF fusion proteins strongly overexpressed using highly active promoters have been investigated. Here, the intracellular distributions of fluorescent PpROP1 and PpROP-GEF4 fusion proteins expressed at essentially endogenous levels in apical cells of Physcomitrella patens “knock-in” protonemata were analyzed. Whereas PpROP-GEF4 was found to associate with a small apical plasma membrane domain, PpROP1 expression was below the detection limit. Estradiol-titratable expression of a fluorescent PpROP1 fusion protein at the lowest detectable level, at which plant development was only marginally affected, was therefore employed to show that PpROP1 also accumulates at the apical plasma membrane, although within a substantially larger domain. Interestingly, RNA-Seq data indicated that the majority of all genes active in protonemata are expressed at lower levels than PpROP1, suggesting that estradiol-titratable expression may represent an important alternative to “knock-in” based analysis of the intracellular distribution of fluorescent fusion proteins in protonemal cells.<br
Keywords: XFP tagging; genomic knock-in; estradiol-inducible expression; Physcomitrella patens; ROP signaling

Evaluation of Reference Genes for RT qPCR Analyses of Structure-Specific and Hormone Regulated Gene Expression in Physcomitrella patens Gametophytes - le Bail, Aude; Scholz, Stefanie; Kost, Benedikt (PLoS ONE, 2013)
The use of the moss Physcomitrella patens as a model system to study plant development and physiology is rapidly expanding. The strategic position of P. patens within the green lineage between algae and vascular plants, the high efficiency with which transgenes are incorporated by homologous recombination, advantages associated with the haploid gametophyte representing the dominant phase of the P. patens life cycle, the simple structure of protonemata, leafy shoots and rhizoids that constitute the haploid gametophyte, as well as a readily accessible high-quality genome sequence make this moss a very attractive experimental system. The investigation of the genetic and hormonal control of P. patens development heavily depends on the analysis of gene expression patterns by real time quantitative PCR (RT qPCR). This technique requires well characterized sets of reference genes, which display minimal expression level variations under all analyzed conditions, for data normalization. Sets of suitable reference genes have been described for most widely used model systems including e. g. Arabidopsis thaliana, but not for P. patens. Here, we present a RT qPCR based comparison of transcript levels of 12 selected candidate reference genes in a range of gametophytic P. patens structures at different developmental stages, and in P. patens protonemata treated with hormones or hormone transport inhibitors. Analysis of these RT qPCR data using GeNorm and NormFinder software resulted in the identification of sets of P. patens reference genes suitable for gene expression analysis under all tested conditions, and suggested that the two best reference genes are sufficient for effective data normalization under each of these conditions.

Molecular Cross-Talk between Gravity-and Light-Sensing Mechanisms in Euglena gracilis - Nasir, Adeel; Richter, Peter; le Bail, Aude; Daiker, Viktor; Stoltze, Julia; Prasad, Binod; Strauch, Sebastian Michael; Lebert, Michael (International Journal of Molecular Sciences, 2022)
Euglena gracilis is a photosynthetic flagellate. To acquire a suitable position in its surrounding aquatic environment, it exploits light and gravity primarily as environmental cues. Several physiological studies have indicated a fine-tuned relationship between gravity sensing (gravitaxis) and light sensing in E. gracilis. However, the underlying molecular mechanism is largely unknown. The photoreceptor photoactivated adenylyl cyclase (PAC) has been studied for over a decade. Never-theless, no direct/indirect interaction partner (upstream/downstream) has been reported for PAC. It has been shown that a specific protein, kinase A (PKA), showed to be involved in phototaxis and gravitaxis. The current study reports the localization of the specific PKA and its relationship with PAC.
CRIS-Team Scopus Importer:2022-03-11
Keywords: Euglena gracilis; Gravitaxis; Indirect immuno-fluorescent assay; Movement analysis; Photoactivated adenylyl cyclase; Phototaxis; Protein kinase A; RNA interference

Physcomitrium patens PpRIC, an ancestral CRIB-domain ROP effector, inhibits auxin-induced differentiation of apical initial cells - Ntefidou, Maria; Eklund, D. Magnus; le Bail, Aude; Schulmeister, Sylwia; Scherbel, Franziska; Brandl, Lisa; Dörfler, Wolfgang; Eichstädt, Chantal; Bannmüller, Anna; Ljung, Karin; Kost, Benedikt (Cell Reports, 2023)
RHO guanosine triphosphatases are important eukaryotic regulators of cell differentiation and behavior. Plant ROP (RHO of plant) family members activate specific, incompletely characterized downstream signaling. The structurally simple land plant Physcomitrium patens is missing homologs of key animal and flowering plant RHO effectors but contains a single CRIB (CDC42/RAC interactive binding)-domain-containing RIC (ROP-interacting CRIB-containing) protein (PpRIC). Protonemal P. patens filaments elongate based on regular division and PpROP-dependent tip growth of apical initial cells, which upon stimulation by the hormone auxin differentiate caulonemal characteristics. PpRIC interacts with active PpROP1, co-localizes with this protein at the plasma membrane at the tip of apical initial cells, and accumulates in the nucleus. Remarkably, PpRIC is not required for tip growth but is targeted to the nucleus to block caulonema differentiation downstream of auxin-controlled gene expression. These observations establish functions of PpRIC in mediating crosstalk between ROP and auxin signaling, which contributes to the maintenance of apical initial cell identity.
CRIS-Team Scopus Importer:2023-02-24
Keywords: auxin; cell differentiation; CP: Developmental biology; CP: Plants; CRIB domain; initial cells; land plant evolution; nuclear targeting; Physcomitrium patens; RHO/ROP effectors; RHO/ROP GTPases; tip growth

Transcriptome profiling of tobacco (Nicotiana tabacum) pollen and pollen tubes - Conze, Lei Liu; Berlin, Sofia; le Bail, Aude; Kost, Benedikt (BMC Genomics, 2017)
<div class="AbstractSection" id="ASec1" style="box-sizing: border-box; color: rgb(51, 51, 51); font-family: "Open Sans"; font-size: medium;" xmlns="http://www.w3.org/1999/xhtml" xmlns:func="http://oscar.fig.bmc.com"> Background Pollen tube growth is essential for plant reproduction and represents a widely employed model to investigate polarized cell expansion, a process important for plant morphogenesis and development. Cellular and regulatory mechanisms underlying pollen tube elongation are under intense investigation, which stands to greatly benefit from a comprehensive understanding of global gene expression profiles in pollen and pollen tubes. Here, RNA sequencing technology was applied to de novo assemble a Nicotiana tabacum male gametophytic transcriptome and to compare transcriptome profiles at two different stages of gametophyte development: mature pollen grains (MPG) and pollen tubes grown for six hours in vitro (PT6). <div class="AbstractSection" id="ASec2" style="box-sizing: border-box; color: rgb(51, 51, 51); font-family: "Open Sans"; font-size: medium;" xmlns="http://www.w3.org/1999/xhtml" xmlns:func="http://oscar.fig.bmc.com"> Results De novo assembly of data obtained by 454 sequencing of a normalized cDNA library representing tobacco pollen and pollen tube mRNA (pooled mRNA isolated from mature pollen grains [MPG] and from pollen tubes grown in vitro for 3 [PT3] or 6 [PT6] hours) resulted in the identification of 78,364 unigenes. Among these unigenes, which mapped to 24,933 entries in the Sol Genomics Network (SGN) N. tabacum unigene database, 24,672 were predicted to represent full length cDNAs. In addition, quantitative analyses of data obtained by Illumina sequencing of two separate non-normalized MPG and PT6 cDNA libraries showed that 8979 unigenes were differentially expressed (differentially expressed unigenes: DEGs) between these two developmental stages at a FDR q-value of <0.0001. Interestingly, whereas most of these DEGs were downregulated in PT6, the minor fraction of DEGs upregulated in PT6 was enriched for GO (gene ontology) functions in pollen tube growth or fertilization. <div class="AbstractSection" id="ASec3" style="box-sizing: border-box; color: rgb(51, 51, 51); font-family: "Open Sans"; font-size: medium;" xmlns="http://www.w3.org/1999/xhtml" xmlns:func="http://oscar.fig.bmc.com"> Conclusions A major output of our study is the development of two different high-quality databases representing the tobacco male gametophytic transcriptome and containing encompassing information about global changes in gene expression after pollen germination. Quantitative analyses of these databases 1) indicated that roughly 30% of all tobacco genes are expressed in the male gametophyte, and 2) support previous observations suggesting a global reduction of transcription after pollen germination. Interestingly, a small number of genes, many of which predicted to function in pollen tube growth or fertilization, were found to be upregulated in elongating pollen tubes despite globally reduced transcription.
Keywords: Tobacco; Pollen; Pollen tube growth; Polar cell expansion; RNA-seq